2018
DOI: 10.1002/jcb.27253
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of SOX6 gene using CRISPR/Cas9 technology for gamma‐globin reactivation: An approach towards gene therapy of β‐thalassemia

Abstract: Elevation of Hemoglobin F ameliorates symptoms of β-thalassemia, a common autosomal recessive disorder. The transcription factor SOX6 plays a key role in the γ to β-globin gene switching. In the current investigation, a mutation was induced using the CRISPR/Cas9 technology in the binding domain region of SOX6 to reactivate γ-globin expression. Three CRISPR/Cas9 cassettes were provided, whose single-guide RNAs targeted different regions in the SOX6 gene-binding domain. After transfection of K562 cells with CRIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 40 publications
0
22
0
1
Order By: Relevance
“…Various transcription factors are important in switching gene expression from γ-globin to β-globin. Shariati et al (111) described one such transcription factor, SOX6. A mutation was introduced in the SOX6 binding gene region with the γ-globin gene promoter using CRISPR/Cas9 preventing its binding, and this resulted in reactivation of γ-globin gene expression.…”
Section: Gene-based Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various transcription factors are important in switching gene expression from γ-globin to β-globin. Shariati et al (111) described one such transcription factor, SOX6. A mutation was introduced in the SOX6 binding gene region with the γ-globin gene promoter using CRISPR/Cas9 preventing its binding, and this resulted in reactivation of γ-globin gene expression.…”
Section: Gene-based Therapiesmentioning
confidence: 99%
“…Increased levels of γ-globin mRNA expression was observed in K562 cells transfected with the CRISPR/Cas9 vectors. Thus, CRISPR/Cas9 can be used as a therapeutic approach for treating patients with β-thalassemia (111). It is hypothesized that the CRISPR/Cas9 system may be used to correct specifically harmful mutations of the HBB gene, and this could be confirmed by normal erythrocyte differentiation and their normal expression.…”
Section: Gene-based Therapiesmentioning
confidence: 99%
“…The transcription factor Sox6 is a pivotal gene in switching the γ to β-globin gene. Shariati et al (2018), reported that disruption of Sox6 binding domain results in the reactivation of γ globin expression. This study concluded that silencing Sox6 may become therapeutic strategy for β-thalassemia treatment (Modares Sadeghi et al, 2018;Shariati et al, 2018).…”
Section: Diseasesmentioning
confidence: 99%
“…(2018), reported that disruption of Sox6 binding domain results in the reactivation of γ globin expression. This study concluded that silencing Sox6 may become therapeutic strategy for β‐thalassemia treatment (Modares Sadeghi et al., 2018; Shariati et al., 2018). Another study showed the functional importance of a number of miRNAs and their target Sox6 in hereditary persistence of fetal hemoglobin deletion type‐2 (HPFH‐2) and Sicilian‐δβ‐thalassemia diseases (Fornari et al., 2017).…”
Section: Sox6 and Cardiovascular Diseasesmentioning
confidence: 99%
“…There are some novel therapeutic tools that are capable of target therapy in different context . Aptamers as one of those therapeutic tools are single‐stranded DNA (ssDNA) or RNA molecules that are typically less than 100‐mer, which have the ability to bind to a wide range of targets, with high affinity and specificity .…”
Section: Introductionmentioning
confidence: 99%